Effect of polystyrenesulphonate and electrolyte concentration for electrical properties of polypyrrole film on aluminium alloy using conductive AFM. (October 2014) - Jung, H. S.; Kim, K. S.; Kwak, M. K.; Ko, J. H.
<x content-type="archive" xml:space="preserve">Abstract</x> The electrochemical synthesis of polystyrenesulphonate (PSS) doped polypyrrole (PPy) film onto aluminium alloy (AA 2024-T3) under galvanostatic conditions at current densities of 1 mA cm−2 was studied. In this study, conductive atomic force microscopy (C-AFM) was performed to investigate the electrical properties of PPy film on AA 2024-T3 depending on the concentration of PSS as dopant and nitric acid as electrolyte during electrochemical synthesis. The addition of HNO3 to aqueous electrolyte solution is found to allow the electrochemical synthesis of well adhering homogeneous PPy film in the presence of PSS on AA 2023-T3. The PPy film in the presence of nitric acid alone can be synthesised, although this film showed the poor quality of the electrical properties of PPy film. According to C-AFM, the study confirmed that the conductivity of PPy film is significantly increased with increasing the PSS, nitric acid concentration and electrochemical deposition time.